Doping Types of Athletics Sportsmen and Determination of the Opinions About Anti-Doping - Celebi, Evrim; Gundogdu, Cemal; Beyazcicek, Ozge; Beyazcicek, Ersin; Ozmerdivenli, Recep (Duzce Univ, 2017)
Objective: This research was conducted to determine the level of knowledge of athletics national team athletes about doping types used in sport and their views on anti-doping. Methods: Seven descriptive type studies were conducted with 73 athletes who participating in the Super League Final Competitions and Junior European Champion Club Cup competitions in the Activity Program of the Turkish Athletics Federation and agreeing to participate in the research. Survey form prepared by researchers was used as data collection tool. The data are expressed in numbers and percentages, using the chi-square test in the analysis. Results: 79.5% of the athletes stated that the most stimulants were used in the sport. This was followed by anabolic androgenic steroids with 68.5%, and anti-estrogenic agents with 65.8%. Approximately two-thirds of the athletes said they were well informed about doping by athletes, coaches and administrators (64.4%), and also they had knowledge about it (% 64.4) and had read doping related publications (65.8%). In terms of anti-doping, athlethes find the activities satisfactory of the related institutions and organizations, in particular state (76.7%), federation (82.2%) and clubs (63.0%). Conclusion: As a result, it has been determined that among the participating athletes, the most common types of doping are in which stimulants and anabolicandrogenic steroids, and approximately two-thirds of the athletes said they were well informed about doping by athletes, coaches and administrators, and also think that they had knowledge about it, moreover more than half of the athletes find the activities of the related institutions and organizations satisfactory for the anti-doping.
Keywords: Anabolic-Androgenic Steroids; Beta-Blockers; Cannabinoids; Doping; Narcotic Analgesics